Controlling the Morphology of Polymers Multiple Scales of Structure and Processing - Mitchell, Geoffrey R.; Tojeira, Ana (Springer International Publishing : Imprint: Springer, 2016)
This book focuses on controlling morphology of different scales for polymers. The authors explain the need for successful control of morphology to yield target macroscopic physical properties in the application of polymers to diverse areas such as engineering materials, nanodielectrics and photonic crystals. The book combines specialized chapters with an introduction to the morphology of polymers and the range of experimental techniques available to evaluate it.